1998
DOI: 10.1021/jp9721208
|View full text |Cite
|
Sign up to set email alerts
|

Tunneling Abstraction Reactions of Tritium Atoms with HD and with Mixtures of H2 and D2 in Superfluid and Normal-Fluid 3He−4He Media at 1.3 K

Abstract: The abstraction reactions, T + HD(DH) f HT(DT) + D(H) and T + H 2 (D 2 ) f HT(DT) + H(D) were studied experimentally in liquid 3 He-4 He media at 1.3 K and theoretically using the gas-phase reaction model. The experimental reaction system has two characteristics; one is that the tritium atom (T) is produced from one of the constituents, 3 He, through 3 He(n, p)T nuclear reaction, and the other is that superfluid or normalfluid reaction medium can be chosen arbitrarily by changing the composition and temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 19 publications
1
15
1
Order By: Relevance
“…58 Synthesis of metallic hydrogen (which has been mentioned above) and the reaction of tritium with hydrogen and deuterium in normal liquid helium and in superfluid quantum helium should be noted as the latest achievements of the `extreme' chemistry. 59 It was found that the exceptionally large isotope effects observed in this reaction (this is predictable) are different for normal and quantum helium (this is unexpected). If this finding is confirmed, new and unusual evidence for chemical coherence will be thus obtained.…”
Section: Chemistry Under Extreme and Exotic Conditionsmentioning
confidence: 92%
“…58 Synthesis of metallic hydrogen (which has been mentioned above) and the reaction of tritium with hydrogen and deuterium in normal liquid helium and in superfluid quantum helium should be noted as the latest achievements of the `extreme' chemistry. 59 It was found that the exceptionally large isotope effects observed in this reaction (this is predictable) are different for normal and quantum helium (this is unexpected). If this finding is confirmed, new and unusual evidence for chemical coherence will be thus obtained.…”
Section: Chemistry Under Extreme and Exotic Conditionsmentioning
confidence: 92%
“…In addition, tritium behaves as an isotope of hydrogen since the mass is three times of hydrogen. Tritium is also well known as a radioactive nuclide that emits β-rays, even a trace amount of tritiated products can be detected with high sensitivity [75]. Tritium is often used to measure the kinetic isotope effect on enzyme catalyzed hydrogen transfer [76,77].…”
Section: And Tritiated Tkhs T 2 Sqmentioning
confidence: 99%
“…The isotope effect (k(T + H 2 )/k(T + D 2 )) in this case increases to 7, indicating a partial contribution of tunneling reaction of thermal T atoms. 12) Recently recoil T atoms are produced in the liquid helium at 1.3 K: 13) 3 He + n → T * + proton (12) T * + He → T + He * (13) T + D 2 → DT + D (14) T + H 2 → HT + H.…”
Section: A Large Isotope Effect In Tunneling Reaction Of Tritium Atomsmentioning
confidence: 99%